Influence of Electroplating Time on the Hardness Properties of Nickel-Coated Aluminum - Margono Margono; Cavin Dwi Prasetyo; Moch Chamim; Deni Andriyansyah; Bondan Wiratmoko Budi Santoso; Deslana Avinda Krisna Putra; Arif Surono; Hassan Khamis Hassan (Institut Teknologi Adhi Tama Surabaya, Indonesia, 2026)
This study investigates the effect of electroplating duration on the hardness and coating thickness of nickel layers deposited on aluminum substrates. Nickel electroplating was performed with immersion times of 17, 34, 51, and 68 min to evaluate the correlation between deposition time, microstructural development, and mechanical enhancement. Microstructural analysis revealed a progressive increase in coating thickness from 3 μm, 7 μm, 11 μm, to a maximum of 44 μm as plating duration increased. Correspondingly, surface hardness exhibited a substantial rise, with untreated aluminum showing 69.44 HV, while electroplated specimens achieved 118.32 HV, 191.32 HV, 258.40 HV, and 418.62 HV, respectively. This increase of up to 502% demonstrates that longer electroplating durations produce denser and finer nickel microstructures, contributing significantly to surface strengthening. The findings confirm that nickel electroplating is an effective method for enhancing the mechanical performance and surface quality of aluminum, with deposition time serving as a critical parameter in optimizing coating characteristics.